2021
DOI: 10.3348/kjr.2020.0209
|View full text |Cite
|
Sign up to set email alerts
|

Update on Transradial Access for Percutaneous Transcatheter Visceral Artery Embolization

Abstract: Transfemoral access (TFA) is a widely used first-line approach for most peripheral vascular interventions. Since its introduction in cardiologic and neurointerventional procedures, several advantages of transradial access (TRA) over TFA have been demonstrated, such as patient preference, lower complication rates, early ambulation, and shorter hospital stay. However, studies reporting the safety and efficacy of this approach for peripheral vascular interventions performed by interventional radiologists are rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 61 publications
2
10
0
Order By: Relevance
“…This study demonstrated that the technical and clinical outcomes following RAE via TRA were similar to those of RAE via TFA for the management of iatrogenic renal hemorrhage, with no access site complications, similar fluoroscopy times, and similar radiation exposure. Although embolization itself is not dependent on the route of access, TRA may have several advantages, including patient comfort and a low rate of access site complications, especially in patients with obesity or coagulopathy [5,14]. The demographic characteristics, underlying diseases, and comorbidities of patients in the TRA and TFA groups did not differ significantly.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This study demonstrated that the technical and clinical outcomes following RAE via TRA were similar to those of RAE via TFA for the management of iatrogenic renal hemorrhage, with no access site complications, similar fluoroscopy times, and similar radiation exposure. Although embolization itself is not dependent on the route of access, TRA may have several advantages, including patient comfort and a low rate of access site complications, especially in patients with obesity or coagulopathy [5,14]. The demographic characteristics, underlying diseases, and comorbidities of patients in the TRA and TFA groups did not differ significantly.…”
Section: Discussionmentioning
confidence: 94%
“…The cohort for this study consisted of 43 consecutive patients who underwent RAE for iatrogenic renal hemorrhage via TRA or TFA at Asan Medical Center, a tertiary medical center in Seoul, Korea, between October 2018 and December 2020. Because of the risk of hand ischemia, Barbeau type D waveform was regarded as a contraindication for TRA in patients with radial obstructive complications secondary to poor ulnar compensation [5]. The minimal radial artery diameter for study inclusion was 1.6 mm.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated the advantages of TRA in terms of patient comfort and safety [ 6 13 14 ]. Many interventions can be safely performed via TRA, even in coagulopathies [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transradial artery access (TRA) for percutaneous intervention is known to have fewer complications at the access site, allows early ambulation and hospital discharge, improves patient satisfaction, and offers potential cost savings compared to transfemoral artery access (TFA) [ 4 5 ]. Furthermore, PAE via TRA can provide more advantages for the patient population, because it allows for leg elevation during a potentially long procedure to alleviate lower back pain and early ambulation to help urination, which may be made more difficult by prostate swelling caused by the procedure [ 6 ]. These benefits enable the treatment of patients on an outpatient basis.…”
Section: Introductionmentioning
confidence: 99%